The South American Advances in Submarine Canyons Studies and Their Link to the Ocean Decade - Silva, Marcos V. B.; Araújo, Tereza C. M. (Frontiers in Marine Science, 2021)
Submarine canyons have relevant role for marine ecosystems. They are responsible for oceanographic conditions such as variability of temperature and salinity, sediment transport, nutrients, and even pollutants amongst marine areas. Submarine canyons studies have been growing and reaching prominence due to their importance on the Blue Economy. Initiatives to promote a sustainable development for the ocean have been discussed in the Ocean Decade. Although canyons studies are increasing, how can we interact with the Ocean Decade outcomes as integrated management? Thus, we aim to demonstrate an overview of the advances of submarine canyons studies and their link to the Ocean Decade for South America. We analyzed 160 studies divided into spatiotemporal analysis and study approaches according to the Ocean Decade outcomes. We discuss these articles building a timeline and argumentative topics considering the advances, gaps to predict the future of submarine canyons studies in the Ocean Decade and Blue Economy context.